A Mo, Nb reinforced Fe-C-Cr wear-resistant surfacing alloy and its preparation method and application

By adding a small amount of Mo and Nb elements to the Fe-C-Cr-type wear-resistant surfacing alloy to regulate its proportion, the problem of cost increase caused by the increase of alloy elements is solved, and high wear resistance is achieved under the wear conditions of high-stress crushing dry sand abrasives.

CN118616964BActive Publication Date: 2025-03-25JINAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410847453.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2025-03-25
Estimated Expiration
2044-06-27

AI Technical Summary

Technical Problem

In the prior art, when preparing wear-resistant surfacing alloys, the increase in alloy elements leads to an increase in cost, making it difficult to meet the wear resistance requirements of high-stress crushed dry sand abrasives wear conditions.

Method used

By strictly controlling the amount of alloy elements, only a small amount of Mo and Nb elements are added, and their proportions are adjusted to prepare Mo and Nb-enhanced Fe-C-Cr-type wear-resistant surfacing alloys to achieve a high wear resistance surfacing layer.

Benefits of technology

It significantly saves the use of alloy elements, reduces costs, and provides high wear resistance under high stress crushed dry sand abrasive wear conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118616964B_ABST
    Figure CN118616964B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a Mo and Nb-enhanced Fe-C-Cr wear-resistant surfacing alloy, comprising the following steps: (1) preparing a flux core powder; (2) pre-treating the flux core powder; (3) preparing a wear-resistant welding wire; and (4) preparing a Mo and Nb-enhanced Fe-C-Cr wear-resistant surfacing alloy. The method strictly controls the amount of alloying elements added, and only by adding a small amount of Mo and Nb alloying elements, a highly wear-resistant Fe-C-Cr surfacing alloy suitable for high-stress crushing dry sand abrasive wear conditions can be prepared, which greatly saves the use of alloying elements for surfacing wear-resistant welding wires and significantly reduces costs; the Mo and Nb-enhanced Fe-C-Cr wear-resistant surfacing alloy prepared by the method and the application of the Mo and Nb-enhanced Fe-C-Cr wear-resistant surfacing alloy in high-stress crushing dry sand abrasive wear conditions are also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal wear-resistant materials, and in particular relates to a Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy and a preparation method and application thereof. Background Art

[0002] Wear-resistant materials are known as the "food of industry." Steel wear-resistant materials are widely used in industries such as metallurgy, mining, electricity, coal, transportation, and agricultural machinery. However, wear and tear are inevitable in any industry. Annual wear and tear consumption accounts for about 1 / 3 to 1 / 2 of total energy. About 50% of machine parts fail due to material wear and tear. Wear and tear has become one of the ways of material failure (corrosion, fracture, wear and tear), causing huge economic losses to the national economy.

[0003] Hardfacing is one method for improving the mechanical properties of component surfaces. It offers advantages such as ease of operation and high efficiency, allowing for rapid repair of component surfaces. It is often used to create wear-resistant hardfacing layers on ordinary substrates to meet operating requirements. Currently, commonly used hardfacing techniques include arc hardfacing, laser hardfacing, plasma hardfacing, and electron beam hardfacing. Arc hardfacing offers the lowest cost in terms of application. For the high-stress, dry sand abrasive wear conditions found in mining machinery, adding appropriate alloying elements can improve the wear resistance of hardfacing coatings. However, the increased cost associated with alloying elements has hindered the development of wear-resistant alloys produced by flux-cored arc hardfacing. Therefore, there is an urgent need to develop wear-resistant hardfacing alloys that require minimal alloying elements while still meeting application requirements. Adjusting the effective alloying element ratio can control the type, quantity, and distribution of carbides in the hardfacing alloy, thereby minimizing the total amount of alloying elements added while still achieving a highly wear-resistant hardfacing layer. Summary of the Invention

[0004] The object of the present invention is to provide a method for preparing a Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy. The method strictly controls the amount of alloying elements added. By adding only a small amount of Mo and Nb alloying elements, a highly wear-resistant Fe-C-Cr surfacing alloy suitable for high-stress crushing dry sand abrasive wear conditions can be prepared, which greatly saves the use of alloying elements for surfacing wear-resistant welding wire and significantly reduces costs.

[0005] The present invention also aims to provide a Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy prepared by the above method.

[0006] The last object of the present invention is to provide the application of the Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy in high stress crushing dry sand abrasive wear conditions.

[0007] The first object of the present invention can be achieved by the following technical solution: A method for preparing a Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy, comprising the following steps:

[0008] (1) Preparation of core powder

[0009] Take the raw materials according to the following mass percentage: Cr 3-5.5%, C 0.8-1.2%, Si 0.7-0.9%, Ni <0.5%, V <0.3%, Mo ≤1%, Nb ≤1%, and the balance is Fe;

[0010] The raw materials are prepared and mixed in a bimodal gradation manner of fine powder and coarse powder to obtain core powder;

[0011] (2) Pretreatment of core powder

[0012] The core powder prepared in step (1) is pretreated, wherein the pretreatment comprises: mixing the core powder in a three-dimensional mixer under argon protection, and then reducing the mixed core powder in a vacuum tube furnace in a hydrogen-argon mixture;

[0013] (3) Preparation of wear-resistant welding wire

[0014] The flux core powder pretreated in step (2) is added to the U-shaped steel strip, and processed by a forming process to obtain a wear-resistant welding wire;

[0015] (4) Preparation of Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy

[0016] The wear-resistant welding wire prepared in step (3) is subjected to argon arc surfacing welding on the substrate to finally obtain Mo and Nb reinforced Fe-C-Cr series wear-resistant surfacing alloy.

[0017] The appropriate addition and coordination of alloying elements can effectively control the type of carbides in hardfacing alloys, resulting in highly wear-resistant hardfacing parts. Chromium promotes carbide formation, and the formation of alloy carbides in the matrix improves the distribution and hardness of the carbides. Silicon improves the carbide morphology. Vanadium increases the hardness of the carbides and improves the wear resistance of the casting. Molybdenum increases the hardenability of the matrix, resulting in solid solution strengthening, and the formed carbides enhance the secondary hardening effect. Niobium forms NbC, which has a higher hardness than other common carbides, reaching 2400 HV.

[0018] In the preparation method of the above-mentioned Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy:

[0019] Preferably, in step (1), the raw materials are taken according to the following mass percentages: Cr 3-5.5%, C 0.8-1.2%, Si 0.7-0.9%, Ni 0.1-0.5%, V 0.1-0.3%, Mo 0.1-1%, Nb 0.1-1%, and the balance is Fe, wherein the mass ratio of Mo to Nb is: 0.2-1:1.

[0020] Further preferably, in step (1), the raw materials are taken according to the following mass percentages: Cr 5-5.5%, C 0.8-1.2%, Si 0.7-0.9%, Ni 0.1-0.5%, V 0.1-0.3%, Mo 0.5-1%, Nb 0.5-1%, and the balance is Fe, wherein the mass ratio of Mo to Nb is 0.5-1:1.

[0021] More preferably, in step (1), the raw materials are taken according to the following mass percentages: Cr 5.5%, C 0.9%, Si 0.8%, Ni 0.4%, V 0.2%, Mo 0.9%, Nb 0.9%, and the balance is Fe, wherein the mass ratio of Mo to Nb is 1:1.

[0022] Preferably, in step (1), the raw materials are divided into fine powder and coarse powder according to particle size, the particle size of the fine powder is 150-175 μm, and the particle size of the coarse powder is 175-300 μm, wherein the fine powder accounts for 40% of the total mass of the fine powder and the coarse powder.

[0023] Preferably, the pretreatment in step (1) includes mixing the core powder and reducing the mixed core powder.

[0024] Preferably, the mixing of the core powder comprises mixing the core powder in a three-dimensional mixer under argon protection.

[0025] Preferably, the reducing and mixing the core powder comprises: subjecting the mixed core powder to a reduction treatment in a vacuum tube furnace and a hydrogen-argon mixed gas.

[0026] Preferably, the rotation speed of the three-dimensional mixer in step (2) is 12 to 24 r / min, and the mixing time is 4 to 6 hours.

[0027] The alloy powder is mixed evenly using a three-dimensional mixing method without destroying the powder particle size and properties.

[0028] Preferably, the heating rate of the vacuum tube furnace in step (2) is 5-10°C / min, and the temperature is maintained for 0.5-2h after reaching the set temperature, and the set temperature is 700-950°C; the flow rate of the hydrogen-argon mixture is 20-50mL / min, and the volume percentage of hydrogen in the hydrogen-argon mixture is 5-20%. More preferably, the volume percentage of hydrogen in the hydrogen-argon mixture is 10-20%.

[0029] Preferably, the filling rate of the core powder in step (3) is 30-55% (the percentage of the core powder in the total mass of the U-shaped steel strip), and more preferably, the filling rate of the core powder is 30-45%.

[0030] Preferably, the forming process in step (3) includes rolling, drawing and other forming processes.

[0031] Preferably, the diameter of the wear-resistant welding wire in step (3) is 3 to 6 mm, more preferably, the diameter of the wear-resistant welding wire is 4 to 5 mm.

[0032] Preferably, the substrate in step (4) is Q235 steel.

[0033] Preferably, during the argon arc surfacing in step (4), the welding current is 200-300 A, the welding voltage is 25-35 V, the welding speed is 180-250 mm / min, the wire feeding speed is 160-270 mm / min, the welding gas flow rate is 20-30 L / min, and high-purity argon gas with a mass percentage of 99.999% is used.

[0034] More preferably, during the argon arc surfacing in step (4), the welding current is 240-270A, the welding voltage is 25-30V, the welding speed is 180-210mm / min, the wire feeding speed is 180-220mm / min, the welding gas flow rate is 20-25L / min, and high-purity argon gas with a mass percentage of 99.999% is used.

[0035] Preferably, the surface macrohardness of the Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy in step (4) is 63-65HRC, and the microhardness is 1400-1495HV1, and the carbides generated are mainly NbC and M7C3 carbides, where M refers to alloy elements, especially Mo and Nb elements, and may also include metal elements such as Ni and V.

[0036] The second object of the present invention can be achieved by the following technical solution: A Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy is prepared by the above method.

[0037] The last object of the present invention can be achieved by the following technical solution: application of the above-mentioned Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy in high stress crushing dry sand abrasive wear conditions.

[0038] Compared with the prior art, the present invention has the following advantages:

[0039] (1) The Mo and Nb reinforced Fe-C-Cr wear-resistant hardfacing alloy of the present invention has a relatively small amount of alloying elements added, with only a small amount of Mo and Nb elements being used as the main alloying elements. By adjusting the addition ratio of Mo and Nb, a highly wear-resistant hardfacing alloy is obtained;

[0040] (2) The Fe-C-Cr wear-resistant welding wire reinforced with a small amount of Mo and Nb elements in the present invention can be used to prepare a high-wear-resistant surfacing alloy under high-stress crushing three-body abrasive wear conditions, which greatly saves costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.

[0042] Figure 1 A comparison chart of the nanohardness of the surfacing alloys prepared in Example 1, Example 4, and Example 5 is shown;

[0043] Figure 2 The XRD patterns of the surfacing alloys prepared in Example 1, Example 4 and Example 5 are shown;

[0044] Figure 3 The metallographic structures of the surfacing alloys prepared in Example 1, Example 4 and Example 5 are shown;

[0045] Figure 4 The morphology of the surfacing alloys prepared in Example 1, Example 4 and Example 5 under a scanning electron microscope is shown. DETAILED DESCRIPTION

[0046] The following is a further description of specific embodiments of the present invention. It should be noted that the description of these embodiments is intended to facilitate understanding of the present invention and does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below may be combined with each other as long as they do not conflict with each other.

[0047] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0048] Unless otherwise specified, the experimental methods used in the following implementation methods are all conventional experimental methods.

[0049] Unless otherwise specified, the terms used in the following implementation methods and examples generally have the meanings commonly understood by those skilled in the art.

[0050] Part 1 Mo, Nb reinforced Fe-C-Cr wear-resistant surfacing alloy and its preparation method

[0051] Example 1

[0052] The preparation method of the Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy provided in this embodiment includes the following steps:

[0053] (1) Preparation of core powder

[0054] The commercially available raw material powders were weighed according to the following mass percentages: Cr 5.5%, C 0.9%, Si 0.8%, Ni 0.4%, V 0.2%, Mo 0.9%, Nb 0.9%, with the mass ratio of Mo to Nb being 1:1 and the balance being Fe.

[0055] The particle size of the fine powder in each raw material is 175 μm, and the particle size of the coarse powder is 250 μm, wherein the fine powder accounts for 40% of the total mass of the fine powder and the coarse powder. The two are mixed to obtain the core powder.

[0056] (2) Core powder pretreatment

[0057] The core powder was mixed in a three-dimensional mixer under argon protection; the speed of the three-dimensional mixer was 24 r / min and the mixing time was 4 h;

[0058] After mixing, the core powder is taken out and placed in a vacuum tube furnace and reduced by introducing 10% hydrogen-argon mixed gas (hydrogen accounts for 10% of the total volume of the mixed gas). The flow rate of the hydrogen-argon mixed gas is 50 mL / min, and the heating rate of the tube furnace is 5°C / min. After reaching the set temperature, keep warm for 1 hour and then take it out. The set temperature is 950°C.

[0059] (3) Preparation of Mo and Nb reinforced Fe-C-Cr welding wire

[0060] The cold-rolled steel strip is used as the outer skin, and the steel strip is bent into a U shape by equipment. The pretreated flux core powder is then added to the U-shaped steel strip through a powder feeder. The flux core filling rate is 30% (that is, the flux core powder accounts for 30% of the total mass of the U-shaped steel strip). The steel strip is rolled into an O shape, and after rolling, drawing and other forming processes, a wear-resistant welding wire with a diameter of 3mm is obtained.

[0061] (4) Preparation of Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy.

[0062] The prepared wear-resistant welding wire was subjected to argon arc surfacing welding on the base material of Q235 steel. The welding current was 260A, the welding voltage was 27V, the welding speed was 180mm / min, the wire feeding speed was 160mm / min, the welding gas flow rate was 20L / min, and 99.999% (mass percentage) high-purity argon gas was used to finally obtain Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy.

[0063] Example 2

[0064] The preparation method of the Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy provided in this embodiment includes the following steps:

[0065] (1) Preparation of core powder

[0066] The commercially available raw material powders were weighed according to the following mass percentages: Cr 5.2%, C 0.9%, Si 0.8%, Ni 0.35%, V 0.21%, Mo 0.9%, Nb 0.9%, with the mass ratio of Mo to Nb being 1:1 and the balance being Fe.

[0067] The particle size of the fine powder in each raw material is 165 μm, and the particle size of the coarse powder is 275 μm, wherein the fine powder accounts for 40% of the total mass of the fine powder and the coarse powder. The two are mixed to obtain the drug core powder.

[0068] (2) Core powder pretreatment

[0069] The powder cores were mixed in a three-dimensional mixer under argon protection; the speed of the three-dimensional mixer was 24 r / min and the mixing time was 4.5 h;

[0070] After mixing, the core powder is taken out and placed in a vacuum tube furnace and reduced by introducing 15% hydrogen-argon mixed gas (hydrogen accounts for 15% of the total volume of the mixed gas). The flow rate of the hydrogen-argon mixed gas is 50 mL / min, and the heating rate of the tube furnace is 5°C / min. After reaching the set temperature, keep warm for 1 hour and then take it out. The set temperature is 950°C.

[0071] (3) Preparation of Mo and Nb reinforced Fe-C-Cr welding wire

[0072] The cold-rolled steel strip is used as the outer skin, and the steel strip is bent into a U shape by equipment. The pretreated flux core powder is then added to the U-shaped steel strip through a powder feeder. The flux core filling rate is 35% (that is, the flux core powder accounts for 35% of the total mass of the U-shaped steel strip). The steel strip is rolled into an O shape, and after rolling, drawing and other forming processes, a wear-resistant welding wire with a diameter of 3mm is obtained.

[0073] (4) Preparation of Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy.

[0074] The prepared wear-resistant welding wire was subjected to argon arc surfacing welding on the base material of Q235 steel. The welding current was 270A, the welding voltage was 30V, the welding speed was 185mm / min, the wire feeding speed was 165mm / min, the welding gas flow rate was 22L / min, and 99.999% high-purity argon was used to finally obtain Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy.

[0075] Example 3

[0076] The preparation method of the Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy provided in this embodiment includes the following steps:

[0077] (1) Preparation of core powder

[0078] The commercially available raw material powders were weighed according to the following mass percentages: Cr 5.1%, C 0.9%, Si 0.8%, Ni 0.38%, V 0.25%, Mo 0.9%, Nb 0.9%, with the mass ratio of Mo to Nb being 1:1 and the balance being Fe.

[0079] The particle size of the fine powder in each raw material is 175 μm, and the particle size of the coarse powder is 275 μm, wherein the fine powder accounts for 40% of the total mass of the fine powder and the coarse powder. The two are mixed to obtain the core powder.

[0080] (2) Core powder pretreatment

[0081] The core powder was mixed in a three-dimensional mixer under argon protection; the speed of the three-dimensional mixer was 24 r / min and the mixing time was 5 h;

[0082] After mixing, the core powder is taken out and placed in a vacuum tube furnace and reduced by introducing 15% hydrogen-argon mixed gas (hydrogen accounts for 15% of the total volume of the mixed gas). The flow rate of the hydrogen-argon mixed gas is 50 mL / min, and the heating rate of the tube furnace is 10°C / min. After reaching the set temperature, keep warm for 1 hour and then take it out. The set temperature is 900°C.

[0083] (3) Preparation of Mo and Nb reinforced Fe-C-Cr welding wire

[0084] The cold-rolled steel strip is used as the outer skin, and the steel strip is bent into a U shape by equipment. The pretreated flux core powder is then added to the U-shaped steel strip through a powder feeder. The flux core filling rate is 38% (that is, the flux core powder accounts for 38% of the total mass of the U-shaped steel strip). The steel strip is rolled into an O shape, and after rolling, drawing and other forming processes, a wear-resistant welding wire with a diameter of 3mm is obtained.

[0085] (4) Preparation of Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy.

[0086] The prepared wear-resistant welding wire was subjected to argon arc surfacing welding on the base material of Q235 steel. The welding current was 260A, the welding voltage was 31V, the welding speed was 185mm / min, the wire feeding speed was 170mm / min, the welding gas flow rate was 20L / min, and 99.999% high-purity argon was used to finally obtain Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy.

[0087] Example 4

[0088] Compared with Example 1, the difference is that the Mo content is 0.45%, the Nb content is 0.9%, and the mass ratio of Mo to Nb is 0.5:1.

[0089] Example 5

[0090] Compared with Example 1, the difference is that the Mo content is 0.18%, the Nb content is 0.9%, and the mass ratio of Mo to Nb is 0.2:1.

[0091] Comparative Example 1

[0092] Compared with Example 1, the difference is that only 0.9% Mo is added, and no Nb is added.

[0093] Comparative Example 2

[0094] Compared with Example 1, the difference is that only 0.9% of Nb is added, and no Mo is added.

[0095] Comparative Example 3

[0096] Compared with Example 1, the difference is that Mo and Nb are not added.

[0097] Part 2 Microstructure and performance test of Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy

[0098] 1) Mechanical properties test of the surfacing alloys in Examples 1-3

[0099] The hardness tests of the hardfacing alloys in Examples 1-3 were conducted according to the methods specified in GB / T 230.1-2018 Rockwell hardness test for metallic materials and GB / T 4340.1-2009 Vickers hardness test for metallic materials. Seven data points were collected, and the average value was calculated after removing the maximum value. The test results are shown in Table 1. The wear resistance tests of the hardfacing alloys in Examples 1-3 and commercially available Cr26 were conducted according to the rubber wheel method test A of ASTM-G65 abrasive wear test method. The test results are shown in Table 2.

[0100] Table 1 Rockwell hardness values ​​of surfacing alloys prepared in Examples 1-3

[0101] Sample name Example 1 Example 2 Example 3 Rockwell hardness / HRC 64.2 63.6 63.9 <![CDATA[Vickers hardness / HV1]]> 1490.5 1477.1 1449.9

[0102] Table 2 Comparison of wear resistance of surfacing alloys prepared in Examples 1-3 and high chromium cast iron Cr26

[0103] Sample name <![CDATA[Initial mass m0 / g]]> <![CDATA[Mass m1 / g after wear]]> Wear weight loss Δm / g Relative wear resistance ε / times Example 1 163.5187 163.4616 0.0571 1.35 Example 2 165.4062 165.3476 0.0586 1.23 Example 3 164.0128 163.9564 0.0564 1.37 High chromium cast iron Cr26 182.5346 182.4574 0.0772 1

[0104] It can be seen from Table 1 that the hardness of the surfacing wear-resistant alloys prepared in Examples 1-3 is greater than 60HRC, and the surface hardness is relatively high. It can be seen from Table 2 that the wear resistance of the surfacing wear-resistant alloys prepared in Examples 1-3 is better than that of Cr26.

[0105] 2) Mechanical properties test of the surfacing alloys in Example 1 and Examples 4-5

[0106] According to the method of GB / T 230.1-2018 Rockwell hardness test for metallic materials and GB / T4340.1-2009 Vickers hardness test for metallic materials, the hardfacing alloys in Examples 1 and 4-5 were subjected to hardness test. Seven data points were collected for the test, and the average value was taken after removing the maximum value. The test results are shown in Table 3. According to the method of GB / T 21838.1-2008 Instrumented indentation test for metallic materials hardness and material parameters, the hardfacing alloys in Examples 1 and 4-5 were subjected to nanohardness test within the microscopic scale. The results are shown in Table 3. Figure 1 shown.

[0107] Table 3 Rockwell hardness and Vickers hardness values ​​of the surfacing alloys prepared in Example 1 and Examples 4-5

[0108] Sample name Example 1 Example 4 Example 5 Rockwell hardness / HRC 64.2 60.8 59.8 <![CDATA[Vickers hardness / HV1]]> 1490.5 1326.86 1296.58

[0109] As can be seen from Table 3, the macrohardness of Example 1 is 64.2HRC and the Vickers hardness is 1490.5HV1, which are higher than the macrohardness and micro-Vickers hardness of the surfacing alloy in Examples 4-5. Figure 1 It can be seen that under the same indentation depth, the load required for the surfacing alloy in Example 1 is the largest, indicating that its nanohardness is the highest.

[0110] 3) Wear resistance test of the surfacing alloys in Example 1 and Examples 4-5

[0111] According to the NMMB / T 012-2018 three-body abrasive wear test method for metal materials, the surfacing alloys in Examples 1 and 4-5 and commercially available Cr26 high-chromium cast iron were subjected to friction and wear tests under high-stress crushing three-body abrasive wear conditions.

[0112] Specific method: The test load is 5 kg, the abrasive is 60-80 mesh quartz sand, and the sample is pre-ground for 30 minutes before the test to better match the friction pair guide rail of the machine. The machine speed is 30 rpm, the amount of sand worn each time is 4 kg, and the wear time is 30 minutes. After that, the sample is taken out, placed in alcohol and cleaned with ultrasonic waves, blown dry, and weighed on an electronic balance with an accuracy of 0.001g to measure the mass change before and after each test. Cr26 is used as the standard sample. Before the test, the sample is pre-ground for 30 minutes and then weighed to obtain the initial mass m0. The weight taken out and weighed after every 30 minutes of wear is m i (i = 1, 2, ... n), and the difference between the two is the wear weight loss of the test sample, Δm. In this test, the wear condition was calculated based on the results after 2 hours of wear. The wear resistance of each sample is expressed as relative wear resistance ε (ε = standard sample weight loss / test sample weight loss). The wear results are shown in Table 4.

[0113] Table 4 Relative wear resistance of the surfacing alloys and high chromium cast iron Cr26 prepared in Example 1, Example 4 and Example 5 under high stress crushing three-body abrasive wear conditions

[0114] Sample name <![CDATA[Initial mass m0 / g]]> <![CDATA[Mass m4 / g after wear]]> Wear weight loss Δm / g Relative wear resistance ε / times Example 1 119.6167 116.7574 2.8593 1.33 Example 4 122.2748 119.1463 3.1285 1.21 Example 5 121.7411 118.5407 3.2004 1.18 High chromium cast iron Cr26 123.3631 119.5677 3.7954 1

[0115] As can be seen from Table 4, under the condition of high stress crushing three-body abrasive wear, the wear resistance of the surfacing alloys in Example 1 and Examples 4-5 is better than that of high chromium cast iron Cr26, and the wear resistance of Example 1 is the highest among the four alloys.

[0116] 4) XRD test of the surfacing alloys in Example 1 and Example 4-5

[0117] According to the test method in GB / T5618-2014 X-ray diffraction analysis method and technical conditions, the surfacing alloys in Example 1 and Example 4-5 were subjected to XRD phase testing. The results are as follows: Figure 2 shown.

[0118] from Figure 2 It can be seen from the figure that the physical composition of the surfacing alloy is mainly α-Fe, γ-Fe and M7C3 (M refers to alloying elements) carbides. The addition of Mo and Nb elements reduces the γ phase region and expands the α phase region. Therefore, the α-Fe peak is higher in Example 1, followed by Example 4. Mo and Nb are refractory carbide-forming elements. At the same carbon content and chromium-carbon ratio, M7C3 is generated in Example 1 and Examples 4-5. At the same time, NbC with higher hardness appears in Example 1.

[0119] 5) Analysis of the microstructure of the surfacing alloys in Example 1 and Examples 4-5

[0120] According to the metal microstructure inspection method of GB / T 13298-2015, the metallurgical structure of the surfacing alloys in Example 1 and Examples 4-5 was observed. Figure 3 According to the test method in GB / T 20307-2006, the surface morphology of the surfacing alloys in Example 1 and Examples 4-5 was observed by scanning electron microscope. Figure 4 shown.

[0121] from Figure 3 It can be seen that there is no obvious grain boundary in Example 1 and Example 4, and the carbides are dispersed in the matrix. This is because the increase of alloy elements and the diffusion of elements in the surfacing pool reaction process promote the precipitation of carbides. The grain boundary is a channel for rapid atomic diffusion. A large amount of carbides precipitate along the grain boundary, making the grain boundary gradually blurred and promoting grain refinement.

[0122] Since the hardness and wear resistance of the surfacing alloy are mainly determined by the structure of the surfacing alloy, in order to improve the wear resistance of the alloy, it is generally necessary to control the formation of a harder martensite phase and an even harder carbide phase in the structure. Figure 4 It can be seen that martensite structure was observed in the surfacing alloys of Examples 4-5. Although martensite structure was not directly observed in Example 1, it can be inferred from the above XRD pattern that martensite exists in the matrix. At the same time, more carbides and dispersed Nb-rich phases were observed in Example 1. At the same carbon content and chromium-carbon ratio, since the affinity of Mo and Nb elements to C element is greater than that of Cr element, most of the Mo and Nb elements first enter the carbides to form M7C3 during the surfacing solidification process. As the carbon element decreases, the formation of alloy carbides tends to be saturated. At the same time, the small amount of Mo element is consumed first, and the remaining part of Nb forms NbC with higher hardness. A small amount of Nb that is not compatible with carbon enters the matrix, plays a role of solid solution strengthening in the matrix, and precipitates dispersed Nb-rich phases to further strengthen the matrix. This combination of martensite + carbides (M7C3 and a small amount of NbC) + Nb-rich strengthening phase improves the hardness and wear resistance of the surfacing alloy. Therefore, the wear resistance of the surfacing alloy can be improved by changing the ratio of Mo and Nb in the flux core powder to around 1:1 and regulating the type and distribution of carbides.

[0123] 6) Mechanical properties test of the surfacing alloys in Example 1 and Comparative Examples 1-3

[0124] According to GB / T 230.1-2018 Rockwell hardness test for metallic materials, the hardness of the surfacing alloys in Example 1 and Comparative Examples 1-3 was tested. Seven data points were collected for the test, and the average value was taken after removing the maximum value. The test results are shown in Table 5.

[0125] According to the rubber wheel method test A in the ASTM-G65 abrasive wear test method, the surfacing alloys in Example 1 and Comparative Examples 1-3 and commercially available Cr26 were subjected to wear resistance tests. The test results are shown in Table 6.

[0126] Table 5 Rockwell hardness values ​​of the surfacing alloys prepared in Example 1 and Comparative Examples 1-3

[0127] Sample name Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Rockwell hardness / HRC 64.2 58.6 59.1 58.4

[0128] It can be seen from Table 5 that the macro hardness of the surfacing alloys prepared in Comparative Examples 1-3 is less than 60 HRC, which is much lower than the hardness of the surfacing alloy prepared in Example 1 (64.2 HRC).

[0129] Table 6 Comparison of wear resistance of surfacing alloys prepared in Example 1 and Comparative Examples 1-3 and high chromium cast iron Cr26

[0130] Sample name <![CDATA[Initial mass m0 / g]]> <![CDATA[Mass m1 / g after wear]]> Wear weight loss Δm / g Relative wear resistance ε / times Example 1 163.5187 163.4616 0.0571 1.35 Comparative Example 1 163.8543 163.6957 0.1586 0.49 Comparative Example 2 164.4172 164.3216 0.0956 0.81 Comparative Example 3 166.2378 165.9327 0.3051 0.25 High chromium cast iron Cr26 182.5346 182.4574 0.0772 1

[0131] As can be seen from Table 6, the wear resistance of the surfacing alloy in Example 1 is higher than that of the surfacing alloys prepared in Comparative Examples 1-3. At the same time, the wear resistance of the surfacing alloys in Comparative Examples 1-3 is lower than that of high chromium cast iron Cr26, indicating that the addition of Mo and Nb and a reasonable mass ratio can enhance the wear resistance of the Fe-C-Cr based surfacing alloy.

[0132] The above embodiments are only used to illustrate the present invention, and the scope of protection of the present invention is not limited to the above embodiments. Those skilled in the art can achieve the purpose of the present invention based on the above disclosure of the present invention. Any improvements and modifications based on the concept of the present invention fall within the scope of protection of the present invention, and the specific scope of protection shall be subject to the claims.

Claims

1. A method for preparing a Mo and Nb reinforced Fe-C-Cr wear-resistant cladding alloy, characterized in that: The following steps are involved: (1) Preparation of core powder The raw materials are taken according to the following mass percentage: Cr 3-5.5%, C 0.8-1.2%, Si 0.7-0.9%, Ni 0.1-0.5%, V0.1-0.3%, Mo 0.5-1%, Nb 0.5-1%, and the balance is Fe, wherein the mass ratio of Mo to Nb is 0.5-1:1; The raw materials are prepared and mixed in a bimodal grading manner of fine powder and coarse powder to obtain a core powder; (2) Pretreatment of core powder The core powder prepared in step (1) is pretreated, wherein the pretreatment comprises: mixing the core powder with a three-dimensional mixer under argon protection, and then reducing the mixed core powder in a vacuum tube furnace and a hydrogen-argon mixed gas; (3) Preparation of wear-resistant welding wire The flux core powder pretreated in step (2) is added into the U-shaped steel strip, and processed by a forming process to obtain a wear-resistant welding wire; (4) Preparation of Mo and Nb reinforced Fe-C-Cr wear-resistant cladding alloy Performing argon arc surfacing welding on the substrate with the wear-resistant welding wire prepared in step (3), and finally obtaining a Mo and Nb reinforced Fe-C-Cr series wear-resistant surfacing alloy; The wear-resistant surfacing alloy is a combination of martensite, carbide, and Nb-rich strengthening phase, wherein the carbide is M7C3 and NbC, and M refers to an alloying element.

2. The method for preparing the Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy according to claim 1, characterized in that: In step (1), the raw materials are divided into fine powder and coarse powder according to their particle size. The particle size of the fine powder is 150-175 μm, and the particle size of the coarse powder is 175-300 μm, wherein the fine powder accounts for 40% of the total mass of the fine powder and the coarse powder.

3. The method for preparing the Mo and Nb reinforced Fe-C-Cr wear-resistant cladding alloy according to claim 1, characterized in that: The rotation speed of the three-dimensional mixer in step (2) is 12-24 r / min, and the mixing time is 4-6 h.

4. The method for preparing the Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy according to claim 1, characterized in that: The heating rate of the vacuum tube furnace in step (2) is 5-10°C / min, and after reaching the set temperature, it is kept warm for 0.5-2h, and the set temperature is 700-950°C; the flow rate of the hydrogen-argon mixed gas is 20-50mL / min, and the volume percentage of hydrogen in the hydrogen-argon mixed gas is 5-20%.

5. The method for preparing the Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy according to claim 1, characterized in that: The filling rate of the flux core powder in step (3) is 30-55%; the forming process includes rolling and drawing; and the diameter of the wear-resistant welding wire is 3-6 mm.

6. The method for preparing the Mo and Nb reinforced Fe-C-Cr wear-resistant cladding alloy according to claim 1, characterized in that: The substrate in step (4) is Q235 steel; in step (4), the welding current during argon arc surfacing welding is 200-300A, the welding voltage is 25-35V, the welding speed is 180-250 mm / min, the wire feeding speed is 160-270 mm / min, the welding gas flow rate is 20-30 L / min, and high-purity argon gas with a mass percentage of 99.999% is used.

7. The method for preparing the Mo and Nb reinforced Fe-C-Cr wear-resistant surfacing alloy according to claim 1, characterized in that: The surface macro-hardness of the Mo and Nb reinforced Fe-C-Cr wear-resistant cladding alloy in step (4) is 63-65 HRC, and the micro-hardness is 1400-1495 HV1.

8. A Mo, Nb reinforced Fe-C-Cr wear-resistant surfacing alloy, characterized in that: The method is prepared by any one of claims 1 to 7.

9. Use of the Mo, Nb reinforced Fe-C-Cr wear-resistant cladding alloy according to claim 8 in high stress crushing dry sand abrasive wear conditions.

Citation Information

Patent Citations

  • Flux-cored wire for surfacing additive of fan-shaped section continuous casting roller as well as preparation method and application of flux-cored wire

    CN116713637A

  • Welding material for build-up welding of 12% chromium steel and build-up welding method using this welding material

    JP1997066389A